PENERAPAN PENYUSUNAN LAPORAN KEUANGAN PADA USAHA KECIL MENENGAH BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (STUDI KASUS GRAHA PONSEL DAN ONE PIECE PONSEL) - Yogi Fathry; Henny Indrawati; R.M. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The preparation of financial statements which is the initial stage of the application of accounting will produce information that has an important role, both for planning, controlling, and for making financial decisions. The Government of Indonesia has specifically regulated the obligations of Small and Medium Enterprises (SMEs) to prepare financial statements for the regulation as outlined in the Financial Accounting Standards for Entities without Public Accountability (SAK ETAP). Graha Ponsel and One Piece Ponsel are MSMEs engaged in trading companies that have made financial reports. The purpose can be taken to determine the appropriateness of the application of the Graha Ponsel and One Piece Ponsel Micro, Small and Medium Enterprises (MSME) financial statements to the Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP). Data analysis techniques use descriptive methods where data is collected, compiled, interpreted and analyzed so as to provide a complete description of the problem at hand. In this study the data collected in the form of financial statements in the form of transactions, balance sheets, income statements, equity reports, cash flow statements, and notes to the financial statements. Then the data is analyzed and compared with the Financial Accounting Standards of the Entity without Public Accountability (SAK ETAP). Graha Ponsel and One Piece Ponsel have not compiled a complete financial report according to SAK ETAP. This is based on SAK ETAP which requires a complete financial statement consisting of a Balance Sheet, Income Statement, Statement of Changes in Equity, Cash Flow Reports, and Notes to Financial Statements. Graha Ponsel and One Piece Ponsel only completes the balance sheet, income statement and equity report sections.Key Words: Financial Accounting , Entities Without Public Accountability